Temporal and Spatial Dynamics of Carbon, Nitrogen, and Phosphorus in a Subtropical Urban River (Tamanduateí River, São Paulo, Brazil) - Flávio H. B. Souza; Mariana Morilla; Beatriz Guedes-Pereira; Kauê Lemes; Ricardo H. Taniwaki (Limnological Review)
Water quality in urban streams often reflects the broader environmental challenges posed by dense population centers, where pollution from untreated sewage and runoff can significantly degrade ecosystems. This study examines the spatial and temporal variations of carbon, nitrogen, and phosphorus concentrations in the Tamanduateí River, which runs through the Metropolitan Region of São Paulo, Brazil. Data were sourced from the annual reports of the Environmental Company of the State of São Paulo (CETESB) covering the period from 2011 to 2022. Between 2011 and 2017, carbon and phosphorus concentrations declined, likely due to sanitation improvements. However, since 2017, these concentrations have been rising again, indicating renewed pollution inputs, primarily from untreated sewage. Nitrogen levels remained consistently high, with elevated concentrations observed upstream, linked especially to domestic effluent discharges. The recent increase in phosphorus levels is also of concern. The absence of spatial variation in phosphorus suggests diffuse pollution from urban areas, while nitrogen decreases downstream, possibly due to biological assimilation. The study underscores the pressing need for enhanced sewage management. Drawing from the successful revitalization of the Cheonggyecheon stream in Seoul, implementing nature-based solutions and regular maintenance could effectively reduce nutrient pollution and improve water quality, facilitating the restoration of the Tamanduateí River.